Comparative advantage of crop-livestock production systems in southwestern Nigeria and its technical research implications - Williams, Timothy O. (Cornell University Press, 1992)
This paper considers the comparative advantage and policy incentives for maize-small ruminant production systems in southwestern Nigeria, using the resource-cost ratio (RCR) approach to analyze the competitiveness and real cost to Nigeria of alternative maize-small ruminant production enterprises. Examines the study area and alley farming systems, the Nigerian policy environment for crop and livestock production, alternatives and data sources, and private and social profitability calculations.